Groundnuts, not tobacco - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
A high-yielding groundnut variety (ICGV-SM 90704) with good resistance against groundnut rosette has come within reach. Rosette is a devastating disease and is always present in the ground-nut crop. A low inci-dence is usually acceptable but in...